Proyecto de inversión para la compra de la franquicia Disensa y su ejecución en la ciudad de Catamayo, de la provincia de Loja - Jumbo Benítez, Consuelo Margarita (2016)
The implementation of the investment project for the implementation of the Disensa San Jose will be held at the Canton Catamayo. The study begins with a general knowledge of the franchise, highlighting the name as the first franchise Disensa Ecuador in Latin America. The research was conducted according to the opinion expressed by the 122 homeowners who requested building permits in the I. Catamayo Canton Township, to whom was identified unmet demand for building materials that can be covered by the San Jose Disensa Co.Ltd. The positioning of the new company will be based on the plan of advertising and corporate identity manual , you will spot radio announcements and advertising , will be advertised in the local press the inauguration, flexible design full color banners , flyers will be delivered , whose budget amounts to $ . 11731.70. The technical study describes the macro and micro localization, identifying the strategic place, in the size referred to the level of investment required for the implementation of the Disensa, physical space adaptations discharge, etc. and describes the machinery with capacities installed. In the financial study detailing the value of the investment in fixed assets, deferred and working capital required , giving a total of $ . 404,041.88, to be funded with a 50.50 % equity and 49.50 %. In determining the economic costs and expenses to be incurred during the five year life of the project. Similarly determines the revenue generated from sales. Then determined the equilibrium point, in the level of sales, in which the San Jose Disensa Co. Ltd., cover their costs and expenses, without incurring either gain or loss. So, in year 1, the Disensa San Jose, working with 34.56% of installed capacity and generated sales revenue of $. 426,081.00 or incurs no loss, no gain , while in year 5 , should work with the 28.58 % and generate an income of $ . 433.953.84 to break even. Finally in the income statement you have a net profit from year one, observing that they decrease for year 2, because the officials are paid the corresponding reserve funds. The financial evaluation of the project, part of the cash flow and has been carried out in two stages: Funded and unfunded on stage with funding financial evaluation indicators are: IRR = $. 51.32 %, NPV = $. 577,145.52, B / C = 2.43, which means that the internal rate of return generated by the project will be $. 51.32 % , which is profitable and much larger than the opportunity cost of capital, the fluid balance be at the end of a project's life, after recovering their investments to cover its costs and expenses will be $ . 577,145.52, the Benefit Cost $. 2.43 means that for every dollar invested in the project earns $. $ 1 to 43 cents. The capital recovery period will be in three years, nine months and seven days. With regard to sensitivity analysis and to find the breaking point, it appears that the project supports a maximum of 6% increase in costs and a decrease in sales of 5%. On stage unfunded financial indicators are: IRR = 43.47 %, NPV = 457,812.72, B / C = $. 2.13, indicating that the project is profitable, the PRC is in 3 years. 8 months and 22 days. The sensitivity analysis, indicates that the project supports maximum 8% increase in costs and a decrease in revenue of 7 %. The conclusions are set to invest in the project is profitable, as seen in the financial evaluation indicators. We recommend running the project preferably funded by the availability of liquidity, low cost of money and credit facilities.